DAMPAK PEMAHAMAN TEOLOGI ANUGERAH TERHADAP PERTUMBUHAN IMAN JEMAAT - Winri Allo Lembang; Mila, Yayu Salom, Riska Andi, Stevi Olan (ADISAM PUBLISHER, 2025)
The understanding of the theology of grace plays a crucial role in the spiritual growth of the congregation. This study aims to analyze the impact of a proper understanding of God's grace on the spiritual development of believers. Using a literature review method, this research examines various theological sources that discuss the concept of grace in the Bible and its implications for the life of faith. The findings indicate that a deep understanding of grace fosters gratitude, reduces legalism, and builds true spiritual freedom. Congregants who recognize that salvation is solely a gift from God are more encouraged to grow in faith, live in love, and serve with pure motivation. Furthermore, the theology of grace helps believers overcome excessive guilt, provides inner peace, and strengthens their faith endurance in facing life’s challenges. This study concludes that a proper understanding of God's grace not only enriches individual spiritual life but also strengthens the congregation as a whole, forming a healthier, more harmonious, and Christ-centered church